APLIKASI PERSEDIAAN LOGISTIK BERBASIS WEBISTE DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Muhammad Nadzir Almunadi; Fahmi Abdullah (Melati Institute, 2023)
Research is an activity carried out by students to fulfill the requirements of the relevant lecturer's assessment. In this research, it is a research to fulfill the requirements before preparing the final project. Research is carried out in an institution or company that has the aim of implementing the results of lectures obtained by students in accordance with their field of expertise. And in this research, the institution or company that is the object of research is the madani orphanage and Tahfidz qur'an institution. research activities are carried out in a period of approximately one month. And for the results of this research is to design and design a simple web-based logistics stock application with the help of website programming language and using the codeigniter framework and also the database used is MySQL which is expected to help ease the activities of the institution. As for what underlies the making of this simple application is because it is found that it still uses manual methods in recording the stock of goods or warehousing activities of the institution.